Idiopathic gastroparesis is associated with specific transcriptional changes in the gastric muscularis externa. Issue 4 (20th October 2017) - Herring, B. P.; Hoggatt, A. M.; Gupta, A.; Griffith, S.; Nakeeb, A.; Choi, J. N.; Idrees, M. T.; Nowak, T.; Morris, D. L.; Wo, J. M.
Abstract: Background: The molecular changes that occur in the stomach that are associated with idiopathic gastroparesis are poorly described. The aim of this study was to use quantitative analysis of mRNA expression to identify changes in mRNAs encoding proteins required for the normal motility functions of the stomach. Methods: Full‐thickness stomach biopsy samples were collected from non‐diabetic control subjects who exhibited no symptoms of gastroparesis and from patients with idiopathic gastroparesis. mRNA was isolated from the muscularis externa and mRNA expression levels were determined by quantitative reverse transcriptase (RT)‐PCR. Key Results: Smooth muscle tissue from idiopathic gastroparesis patients had decreased expression of mRNAs encoding several contractile proteins, such as MYH11 and MYLK1. Conversely, there was no significant change in mRNAs characteristic of interstitial cells of Cajal (ICCs) such as KIT or ANO1. There was also a significant decrease in mRNA‐encoding platelet‐derived growth factor receptor α (PDGFRα) and its ligand PDGFB and in Heme oxygenase 1 in idiopathic gastroparesis subjects. In contrast, there was a small increase in mRNA characteristic of neurons. Although there was not an overall change in KIT expression in gastroparesis patients, KIT expression showed a significant correlation with gastric emptying whereas changes in MYLK1, ANO1 and PDGFRα showed weak correlations to the fullness/satiety subscore of patient assessment of upper gastrointestinal disorder‐symptom severity index scores. Conclusions and Inferences: Our findings suggest that idiopathic gastroparesis is associated with altered smooth muscle cell contractile protein expression and loss of PDGFRα + cells without a significant change in ICCs. Abstract : qRT‐PCR analysis revealed that smooth muscle tissue from idiopathic gastroparesis patients had decreased expression of mRNAs encoding several contractile and regulatory proteins, PDGFRalpha and its ligand PDGFB and Heme oxygenase 1. Conversely, there was no significant change in mRNAs characteristic of interstitial cells of Cajal (ICCs), such as KIT or ANO1. These findings suggest that idiopathic gastroparesis is most commonly associated with transcriptional changes that are indicative of altered smooth muscle cells and PDGFRalpha positive fibroblast cells rather than ICCs.